Comparison of the leaf epidermal micromorphology between female and male Idesia polycarpa Maxim. - YIN Dandan; SU Shang (Xibei zhiwu xuebao, 2024)
Abstract [Objective] The study aims to explore the micromorphological characteristics of leaf epidermis of Idesia polycarpa Maxim. and investigate differences between the female and male plants in order to provide references for the mining and utilization of its germplasm resources. [Methods] The leaf epidermal micro-configurations of 40 plants of I. polycarpa (half female and half male) were characterized with scanning electron microscopy. 12 stomatal traits were measured and the similarities and differences among the samples were analyzed. [Results] (1) The leaf epidermal hair, cell morphology, stomatal characteristics, and wax pattern of both female and male I. polycarpa were similar. The dense, conical conicoid-like wax covered on the abaxial epidermis was rarely observed in other plants. (2) The leaf stomatal size (length, width, area, and perimeter) and density-related parameters of the female I. polycarpa were slightly higher than those of the male samples. On the contrary, leaf stomatal pore-related parameters (stomatal pore width, stomatal opening area, and stomatal opening level) were slightly higher in the male samples. But all differences were not statistically significant (P >0.05). (3) Most stomatal traits were significantly correlated with each other, while stomatal density was rarely related with others, which might be subject to relatively independent genetic regulation. [Conclusion] This study examined the characteristics of leaf epidermal micromorphology of I. polycarpa, and finded that the conical conicoid-like wax pattern could be used for germplasm evaluation, and the stomatal parameters were essential for gender determination of its young seedlings.